TOLERÂNCIA DE VARIEDADES DE ALFAFA SUBMETIDAS À SALINIDADE - Silva, Rodrigo Moura e; Simões, Welson Lima; Guimarães, Miguel Julio Machado; Barros, Juliane Rafaele Alves; Barbosa, Kaio Vinicius Fernandes; Angelotti, Francislene (IRRIGA, 2023)
TOLERANCE OF ALFALFA VARIETIES SUBJECTED TO SALINITY RODRIGO MOURA E SILVA1; WELSON LIMA SIMÕES2; MIGUEL JULIO MACHADO GUIMARÃES3; JULIANE RAFAELE ALVES BARROS4; KAIO VINICIUS FERNANDES BARBOSA5 E FRANCISLENE ANGELOTTI6 1 Universidade de Pernambuco, Rodovia BR 203, Km 2 s/n - Vila Eduardo, 56328-900, Petrolina, Pernambuco, Brasil, e-mail: moura.pnz@gmail.com. 2 Embrapa Semiárido, Rodovia BR-428, Km 152, s/n - Zona Rural, 56302-970, Petrolina, Pernambuco, Brasil, e-mail: welson.simoes@embrapa.br. 3Instituto Federal de Educação, Ciência e Tecnologia, BR-230, 65840-000, São Raimundo das Mangabeiras, Maranhão, Brasil, e-mail: mjmguimaraes@hotmail.com. 4 Fundação de Amaparo à Ciência e Tecnologia do Estado e Pernambuco, Rua Benfica,150, Madalena, 50720-001, Recife, Pernambuco, Brasil, e-mail: juliane-ab@hotmail.com. 5 Universidade de Pernambuco, Rodovia BR 203, Km 2 s/n - Vila Eduardo, 56328-900, Petrolina, Pernambuco, Brasil, e-mail: kaioviniciusfernandesbarbosa@gmail.com. 6 Embrapa Semiárido, Rodovia BR-428, Km 152, s/n - Zona Rural, 56302-970, Petrolina, Pernambuco, Brasil, e-mail: francislene.angelotti@embrapa.br 1 ABSTRACT Saline water can be an alternative for the production of salt-tolerant forages. Thus, the objective was to evaluate the tolerance of alfalfa varieties to salinity, aiming at their inclusion in production systems that use irrigation water with high levels of salt or salinized soils. The experiment was conducted in a greenhouse, in a 3x5x3 factorial, three alfalfa varieties (LE-N4, Crioula and DK-192), five salinity levels (0; 3.5; 5.0; 7.0; 10. 5 and 14.0 dS m-1) and three cuts of the aerial part, with four replications. For irrigation management, lysimeters were installed. Fresh and dry plant biomass, chlorophyll, water use efficiency and enzymatic activity were analyzed. Increased salinity reduced fresh and dry biomass of shoots and roots, chlorophyll content and water use efficiency. Salinity altered the biochemical responses of alfalfa. DK-192 showed higher production of fresh and dry biomass of the shoot, while LE-N4 was more sensitive to saline stress, reducing production from the level of 7.0 dS m-1. Increased catalase activity in Crioula and DK-192 under saline stress contributed to the production of fresh and dry biomass of the shoot. Keywords: Medicago sativa L, saline water, biomass, enzymes, oxidative stress. SILVA, R. M. e.; SIMÕES, W. L.; GUIMARÃES, M. J. M.; BARROS, J. R. A.; BARBOSA, K. V. F.; ANGELOTTI, F. TOLERÂNCIA DE VARIEDADES DE ALFAFA SUBMETIDAS À SALINIDADE 2 RESUMO Água salina pode ser uma alternativa para produção de forrageiras tolerantes ao sal. Assim, objetivou-se avaliar a tolerância de variedades de alfafa à salinidade, visando sua inclusão em sistemas de produção que utilizam água de irrigação com teores de sais elevados ou solos salinizados. O experimento foi conduzido em casa de vegetação, em fatorial 3x5x3, três variedades de alfafa (LE-N4, Crioula e DK-192), cinco níveis de salinidade (0; 3,5; 5,0; 7,0; 10,5 e 14,0 dS m-1) e três cortes da parte aérea, com quatro repetições. Para o manejo da irrigação foram instalados lisímetros. Analisou-se a biomassa fresca e seca da planta, clorofila, eficiência do uso da água e atividade enzimática. O aumento da salinidade reduziu a biomassa fresca e seca da parte aérea e da raiz, conteúdo de clorofila e a eficiência no uso de água. A salinidade alterou as respostas bioquímicas da alfafa. A DK-192 apresentou maior produção de biomassa fresca e seca da parte aérea, a LE-N4 foi mais sensível ao estresse salino, reduzindo a produção a partir do nível de 7,0 dS m-1. O aumento da atividade da catalase na Crioula e DK-192 sob estresse salino contribuiu para produção de biomassa fresca e seca da parte aérea. Palavras-chave: Medicago sativa L, água salina, biomassa, enzimas, estresse oxidativo.